Foreign Intervention in Civil Wars. - Woo, Jung-Yeop (Cambridge Scholars Publishing, 2017)
This book identifies the conditions under which foreign countries intervene in civil wars, contending that we should consider four dimensions of civil war intervention. The first dimension is the civil war itself. The characteristics of the civil war itself are important determinants of a third party's decision making regarding intervention. The second dimension is the characteristics of intervening states, and includes their capabilities and domestic political environments. The third is the relationship between the host country and the intervening country. These states' formal alliances and t.